2011
DOI: 10.1182/blood-2010-11-319186
|View full text |Cite
|
Sign up to set email alerts
|

Differences in clinical outcomes after 2009 influenza A/H1N1 and seasonal influenza among hematopoietic cell transplant recipients

Abstract: It is not known whether pandemic 2009 influenza A/H1N1 (2009 H1N1) leads to more serious disease than seasonal influenza in hematopoietic cell transplant (HCT) recipients. In a retrospective study in HCT recipients with virologically proven influenza virus infection, a total of 161 HCT recipients (18 2009 H1N1, 103 seasonal influenza A, and 40 seasonal influenza B) were analyzed. In multivariable analyses, more patients with 2009 H1N1 had lower respiratory tract disease (LRD), hypoxemia, and prolonged viral sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
147
4
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(166 citation statements)
references
References 43 publications
(56 reference statements)
13
147
4
2
Order By: Relevance
“…These data explain our high mortality rate observed among the 17 patients who were admitted to ICU (11/17; 65%) or among the 12 patients who developed respiratory failure (11/12; 92%). These values are comparable to those reported in the same type of population 1, 8, 12, 22 , but are higher than those reported in other populations, which ranged from 0–24% 21, 2629 . Indeed, the overall mortality rate observed among Argentinean patients admitted to ICU and requiring mechanical ventilation was 46% 25 .…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…These data explain our high mortality rate observed among the 17 patients who were admitted to ICU (11/17; 65%) or among the 12 patients who developed respiratory failure (11/12; 92%). These values are comparable to those reported in the same type of population 1, 8, 12, 22 , but are higher than those reported in other populations, which ranged from 0–24% 21, 2629 . Indeed, the overall mortality rate observed among Argentinean patients admitted to ICU and requiring mechanical ventilation was 46% 25 .…”
Section: Discussionsupporting
confidence: 85%
“…The incidence of pneumonia we found is higher than the one reported with seasonal influenza in cancer patients (5–44%) 3, 1820 and it is also higher than the incidence of lower respiratory tract infections (LRTI) caused by the 2009 pandemic Influenza A H1N1 in the hospitalized general population (40–44%) 21 , in solid organ transplant recipients (23%) 16 , in HCT recipients (21–56%) 1, 6, 8, 1214, 22 and in patients with hematological malignancies (48%) 23 . Only one small study that includes 15 confirmed cases of 2009 pandemic Influenza A H1N1 infection in onco-hematological patients reports a higher incidence of pneumonia (87%) 15 .…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations